Sustainable Human Resource Practices: Analyzing Their Impact on Organizational Resilience and Employee Retention - Muhammad Syafri; Andi Rasyid (Return : Study of Management, Economic and Bussines, 2025)
Human resources (HR) are a critical asset for organizations, and sustainable HR management is essential to fostering organizational resilience and retaining high-quality employees. Sustainable HR practices focus on maintaining the long-term well-being of the workforce while meeting the evolving needs of the organization. This study aims to analyze the impact of sustainable human resource management (HRM) practices on organizational resilience and employee retention, particularly in the Medan area. This study used a quantitative approach using a survey questionnaire distributed to 40 employees from various companies in Medan. The questionnaire assessed aspects of welfare policy, career development, and organizational culture. Data were analyzed using descriptive statistics and simple linear regression. The findings show that sustainable HRM practices significantly positively impact organizational resilience and employee retention. Specifically, an increase in sustainable HR policies was associated with an increase in organizational resilience by 0.45 and employee retention by 0.38. The study concludes that implementing sustainable HRM practices can strengthen organizational stability and improve employee retention in the long run. These insights provide valuable guidance for organizations in designing effective HRM policies that support resilience and retention.